a) x² - x - 12 = 0
b) 6x² + x - 1= 0
c) x² - 2x - 24 = 0
x' = 1+²V1+48/2
x' = 1+²V49/2
x' = 1+7/2
x' = 8/2
x' = 4
x" = 1-7/2
x" = -6/2
x" = -3
x' = -1+²V1+24/12
x' = -1+²V25/12
x' = -1+5/12
x' = 4/12
x' = 1/3
x" = -1-5/12
x" = -6/12
x" = -1/2
x' = 2+²V4+96/2
x' = 2+²V100/2
x' = 2+10/2
x' = 12/2
x' = 6
x" = 2-10/2
x" = -8/2
x" = -4
Comments
x' = 1+²V1+48/2
x' = 1+²V49/2
x' = 1+7/2
x' = 8/2
x' = 4
x" = 1-7/2
x" = -6/2
x" = -3
x' = -1+²V1+24/12
x' = -1+²V25/12
x' = -1+5/12
x' = 4/12
x' = 1/3
x" = -1-5/12
x" = -6/12
x" = -1/2
x' = 2+²V4+96/2
x' = 2+²V100/2
x' = 2+10/2
x' = 12/2
x' = 6
x" = 2-10/2
x" = -8/2
x" = -4